2019
DOI: 10.1055/a-1045-5437
|View full text |Cite
|
Sign up to set email alerts
|

Hawthorn (Crataegus monogyna) Phenolic Extract Modulates Lymphocyte Subsets and Humoral Immune Response in Mice

Abstract: This study investigated the effect of hawthorn (Crataegus monogyna) phenolic extract on lymphocyte subsets in the lymphoid organs in nonimmunized mice and on humoral immune response in sheep red blood cell-immunized mice. Hawthorn phenolic extract (50, 100, 200 mg/kg) was administered orally five or ten times. Sheep red blood cells were injected 24 h after administration of the last extract dose. The lymphocyte subsets were assessed 24 and 72 h after the last dose. Humoral immune response was determined 4 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…The active ingredients in hawthorn are the basis for the wide range of health benefits it exerts ( Table 4 ). For example, polyphenolic compounds are good antioxidants [ 12 ] and immunomodulators [ 75 ], flavonoids have anti-inflammatory [ 76 ] and anti-atherogenic activity [ 77 ], lignans have antibacterial [ 78 ] and antioxidant activity [ 39 ], while triterpenoidshave anticancer [ 79 ], anti-inflammatory, and anti-proliferative activities [ 41 ]. It is therefore essential to advocate the exploitation of the therapeutic potential of hawthorn in new food products to improve and maintain the nutritional and health indices of the population.…”
Section: Health Benefitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active ingredients in hawthorn are the basis for the wide range of health benefits it exerts ( Table 4 ). For example, polyphenolic compounds are good antioxidants [ 12 ] and immunomodulators [ 75 ], flavonoids have anti-inflammatory [ 76 ] and anti-atherogenic activity [ 77 ], lignans have antibacterial [ 78 ] and antioxidant activity [ 39 ], while triterpenoidshave anticancer [ 79 ], anti-inflammatory, and anti-proliferative activities [ 41 ]. It is therefore essential to advocate the exploitation of the therapeutic potential of hawthorn in new food products to improve and maintain the nutritional and health indices of the population.…”
Section: Health Benefitsmentioning
confidence: 99%
“…This is mainly due to the fact that epicatechin and proanthocyanidins B2 and B4 in hawthorn promote the proliferation of splenocytes, significantly increase the percentage of B cells, decrease the percentage of Th cells and stimulate the humoral immune response. And the effect is more pronounced at high doses (100 and 200 mg/kg) of the extract [ 75 ].…”
Section: Health Benefitsmentioning
confidence: 99%
“…These bioactive components in hawthorn, such as flavonoids and terpenoids, were revealed to have physiological functions in the cardiovascular, digestive, and endocrine systems [ 47 ]. It was also found that hawthorn polyphenols could reduce the risks of diabetes [ 48 ], or display an immuno-modulatory effect on the lymphocytes [ 49 ]. In this study, the purslane polysaccharides and two selenylated products were clarified with a clear immune modulation on the two model cells.…”
Section: Discussionmentioning
confidence: 99%
“…A combined blend of leaves, berries and flowers was traditionally administered as an astringent, antispasmodic, cardiotonic, diuretic, hypotensive and anti-atherosclerotic agent. Various extracts of C. monogyna were evaluated for screening in vitro/in vivo models [ 32 , 77 , 78 , 79 , 80 ].…”
Section: Pharmaceutical Propertiesmentioning
confidence: 99%